Behavior Editor for Agents Based on Service Oriented Architecture - Zambiasi, Saulo Popov; Rabelo, Ricardo J. (Anais do Workshop-Escola de Sistemas de Agentes, seus Ambientes e Aplicações (WESAAC), 2013)
Many efforts have been made to create agents more autonomous, flexible and dynamic. Concomitantly with the fact that agents are inserted in environments distributed, interconnected and with a lot of dynamics information, it agents need to communicates with others and other systems by the inter-operable way. The use of a standard, such as Service Oriented Architecture and web services, can provide an inter-operable way to agents communication and to executes some distributed operations. Thus, this paper presents a proposal of a behavior editor for agents based on Service Oriented Architecture. A prototype of a behavior editor and an executor of agents was implemented and it is also presented.